Preparation method of phosphogypsum-based inorganic binder stable material

CN123003205APending Publication Date: 2026-10-30ANHUI INST OF BUILDING RES & DESIGN
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311708703.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-12-13
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0004]本发明的目的是为了解决现有技术中存在的磷石膏利用率低的问题,而提出的一种磷石膏基无机结合料稳定材料的制备方法

Benefits of technology

[0016]本发明的有益效果为:以磷石膏为主要原材料,采用生石灰中和法对酸性磷石膏进行改性。处理之后的磷石膏和级配砾石作为被稳定材料,水泥和粉煤灰作为稳定材料,并按预处理磷石膏:水泥:粉煤灰:骨料:水=50:6:5:39:11的配比制成混合料,其中掺加激发剂CaCl2含量为0.22%,其7天抗压为3.05Mpa,能达到二级及二级以上公路的使用要求,其后期的劈裂强度性能与相关的稳定性能均能满足使用要求。同时对试件的SEM进行分析,反应所存在的C-S-H凝胶和附着于凝胶上的钙矾石晶体的存在,以及一部分六角板状的Ca(OH)2晶体会使得材料强度上升;与传统材料相比,对磷石膏的消耗有很大的帮助,在一定程度上缓解了磷石膏的堆积问题,减轻了生态环境污染问题和磷化工企业的压力,在降低生产成本的同时取得更加显著的经济效益,对促进磷石膏资源可持续发展和建材行业发展提供一定的研究作用。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123003205A_ABST
    Figure CN123003205A_ABST
Patent Text Reader

Abstract

The present application belongs to the field of phosphogypsum inorganic binder, and discloses a preparation method of phosphogypsum-based inorganic binder stable material, which is used to solve the problem of low utilization rate of phosphogypsum in the prior art. The method comprises the following steps: S1: pretreatment of phosphogypsum: using calcium oxide to modify and pretreat the phosphogypsum, and then drying to obtain product one; S2: ball milling and screening: ball milling and screening the product one to obtain product two; S3: preparation of phosphogypsum-based inorganic binder: mixing the raw material, the product two and the activator to obtain product three; S4: curing of the phosphogypsum-based inorganic binder stable material. The present application takes phosphogypsum as the main raw material, and adds the activator CaCl2, so that the phosphogypsum inorganic binder can meet the use requirements of secondary and above secondary roads, to a certain extent, the accumulation problem of phosphogypsum is alleviated, the ecological environment pollution problem and the pressure of phosphorus chemical enterprises are reduced, and more significant economic benefits are achieved while the production cost is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of phosphogypsum inorganic binder technology, and in particular to a method for preparing a phosphogypsum-based inorganic binder stabilized material. Background Technology

[0002] Phosphogypsum is a waste residue generated during the wet process of phosphoric acid production in the phosphate chemical industry. Phosphogypsum has a water content of 12.9% and a pH of 2.75. Its main component is calcium sulfate dihydrate (CaSO4·2H2O), primarily produced during the reaction of sulfuric acid and apatite to produce phosphoric acid. It also generates a small amount of HF. In addition, most phosphogypsum contains unreacted apatite, phosphoric acid, and organic matter containing fluorine and phosphorus, among other impurities. The cumbersome and costly treatment methods for these impurities contribute to the low utilization rate of phosphogypsum and its lack of market appeal.

[0003] Therefore, researching ways to expand the utilization of phosphogypsum resources and improving its utilization rate remains a concern for many scholars. Summary of the Invention

[0004] The purpose of this invention is to solve the problem of low utilization rate of phosphogypsum in the prior art, and to propose a method for preparing phosphogypsum-based inorganic binder stabilized materials.

[0005] To achieve the above objectives, the present invention adopts the following technical solution:

[0006] A method for preparing a phosphogypsum-based inorganic binder stabilized material includes the following steps: S1: Pretreatment of phosphogypsum: Pphosphogypsum is modified and pretreated with calcium oxide and then dried to obtain product one; S2: Ball milling and sieving: Product one is ball milled and then sieved to obtain product two; S3: Preparation of phosphogypsum-based inorganic binder: Raw materials, product two and activator are mixed to obtain product three, the activator being one of NaOH, CaCl2 and Na2CO3. Product three is placed in a mold, compacted, and then demolded to obtain product four; S4: Curing of phosphogypsum-based inorganic binder stabilized material: After curing, product four is soaked in water for 24 hours on days 6, 27 and 89 and then tested accordingly.

[0007] Preferably, in S1, the phosphogypsum has a water content of 12.9%, a pH of 2.75, and the phosphogypsum crystals mainly exhibit regular flaky or prismatic crystals with a particle size distribution between 5 and 100 μm and an average particle size of 45 to 75 μm.

[0008] Preferably, in S1, 0.4 parts of calcium oxide and 11 parts of water are mixed to modify 99.6 parts of phosphogypsum. After the gypsum modification pretreatment, it is allowed to stand at room temperature for 24 hours and then dried in an oven at 80°C for 24 hours.

[0009] Preferably, in step S2, product one is ball-milled using a ball mill and passed through a 1.18 mm sieve.

[0010] Preferably, in step S3, the raw materials include 3 parts cement, 8 parts slag, 39 parts gravel, and 11 parts water; in step S3, the product is 50 parts and the activator is 0-1 parts.

[0011] Preferably, the slag is selected from a concrete mixing plant and is a white powder; the gravel is black gravel aggregate purchased from the market; and the cement is a common hydraulic cementitious material, specifically P·O42.5 silicate cement.

[0012] Preferably, the activator is one of 0.11 parts, 0.22 parts, 0.33 parts, or 0.44 parts; sodium hydroxide, AR analytical grade, 96%, white crystalline powder; calcium chloride, AR analytical grade, 96%, white powder; sodium carbonate, inorganic compound, AR analytical grade, ≥99.5%, white odorless powder or granules at room temperature.

[0013] Preferably, in step S3, product three is placed into a cylindrical mold of 10cm*10cm*10cm, then compacted by a press to a compaction degree of 95%, left to stand for 24 hours, and then demolded by a demolding machine to obtain product four.

[0014] Preferably, in step S4, after the product has been cured, it is soaked in water for 24 hours on days 6, 27, and 89. The test block is then taken out and placed in water for immersion, with the water level 2 cm above the surface of the test block. After soaking for one day, the test block is taken out, the surface moisture is wiped dry with a cloth, and then placed on a press for compressive strength testing.

[0015] Preferably, the testing of the phosphogypsum-based inorganic binder stabilized material includes unconfined compressive strength test, splitting tensile strength test, and wet-dry cycle test.

[0016] The beneficial effects of this invention are as follows: Acidic phosphogypsum is modified using quicklime neutralization as the main raw material. The treated phosphogypsum and graded gravel are used as stabilized materials, while cement and fly ash are used as stabilizing materials. A mixture is prepared according to the ratio of pretreated phosphogypsum:cement:fly ash:aggregate:water = 50:6:5:39:11, with an added activator CaCl2 content of 0.22%. Its 7-day compressive strength is 3.05 MPa, meeting the requirements for Class II and above highways. Its subsequent splitting strength and related stability properties also meet the usage requirements. Simultaneously, SEM analysis of the specimens revealed that the presence of CSH gel and ettringite crystals attached to the gel, as well as some hexagonal plate-shaped Ca(OH)2 crystals, contributes to the increased material strength. Compared with traditional materials, this method significantly reduces the consumption of phosphogypsum, alleviating the problem of phosphogypsum accumulation to some extent, reducing environmental pollution and the pressure on phosphate chemical enterprises. It achieves more significant economic benefits while reducing production costs, and provides a certain research contribution to promoting the sustainable development of phosphogypsum resources and the development of the building materials industry. Attached Figure Description

[0017] Figure 1 This is a flowchart of a method for preparing a phosphogypsum-based inorganic binder stabilized material proposed in this invention;

[0018] Figure 2 This is a schematic diagram showing the pH and P content of phosphogypsum after adding different amounts of quicklime in the preparation method of the phosphogypsum-based inorganic binder stabilized material proposed in this invention.

[0019] Figure 3 This is a schematic diagram of the optimal moisture content and maximum dry density distribution and fitting curve in the preparation method of the phosphogypsum-based inorganic binder stabilized material proposed in this invention.

[0020] Figure 4 This is a diagram showing the proportions of raw materials in a method for preparing a phosphogypsum-based inorganic binder stabilized material proposed in this invention.

[0021] Figure 5 This is a schematic diagram of the unconfined compressive strength of phosphogypsum-based specimens from different dates in the preparation method of a phosphogypsum-based inorganic binder stabilized material proposed in this invention.

[0022] Figure 6 This is a distribution diagram showing the effect of NaOH content on the compressive strength of phosphogypsum-based specimens in the preparation method of the phosphogypsum-based inorganic binder stabilized material proposed in this invention.

[0023] Figure 7This is a distribution diagram showing the effect of NaOH content on the splitting strength of phosphogypsum-based specimens in the preparation method of the phosphogypsum-based inorganic binder stabilized material proposed in this invention.

[0024] Figure 8 This is a graph showing the relationship between the product mass loss rate and the number of wet-dry cycles in the preparation method of a phosphogypsum-based inorganic binder stabilized material proposed in this invention.

[0025] Figure 9 This is a graph showing the changes in compressive strength of the product after 6 and 12 wet-dry cycles in the preparation method of a phosphogypsum-based inorganic binder stabilized material proposed in this invention.

[0026] Figure 10 This is a graph showing the F and Cl ion content data of different activators-phosphogypsum-based specimens in the preparation method of a phosphogypsum-based inorganic binder stabilized material proposed in this invention.

[0027] Figure 11 This is a data graph showing the dissolution of phosphorus in phosphogypsum-based specimens with different activators in the preparation method of the phosphogypsum-based inorganic binder stabilized material proposed in this invention.

[0028] Figure 12 SEM images of each activator at its optimal content in the preparation method of the phosphogypsum-based inorganic binder stabilized material proposed in this invention;

[0029] Figure 13 This is a graph showing the surface variation of a phosphogypsum-based specimen with varying activator content in a method for preparing a phosphogypsum-based inorganic binder stabilized material proposed in this invention. Detailed Implementation

[0030] The technical solutions of the present invention will be clearly and completely described below with reference to the accompanying drawings of the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments.

[0031] This technical solution uses phosphogypsum as the main raw material, along with cement, fly ash, and gravel, and adds an activator to prepare an inorganic binder stabilized material for road base courses. While ensuring the relevant performance of the finished product, the environmental impact of the finished product is studied, and the reaction mechanism of the finished product is investigated. This approach improves the consumption of phosphogypsum and reduces the problem of phosphogypsum accumulation.

[0032] Reference Figures 2-3Phosphogypsum is a brownish-gray powder, mainly composed of CaSO4·2H2O. It lacks gelling properties, is slightly acidic, and requires neutralization with calcium oxide (0.4 parts) to raise the pH and remove impurities. According to current experimental standards, a heavy compaction test was conducted on samples with a fixed phosphogypsum content. Five samples with different moisture contents (9%, 10%, 11%, 12%, and 13%) were used. The inflection points of the moisture content and dry density curves plotted from the compaction tests were used to determine the optimal moisture content and maximum dry density for different proportions. The optimal dry density was found at a moisture content of 11%.

[0033] Reference Figure 4 and Figure 1 Conduct the experiment:

[0034] Example 1: A method for preparing a phosphogypsum-based inorganic binder stabilized material, comprising 0.4 parts calcium oxide, 11 parts water, and 99.6 parts phosphogypsum, which are mixed to modify the phosphogypsum. After the gypsum modification pretreatment, the mixture is allowed to stand at room temperature for 24 hours and then dried in an oven at 80°C for 24 hours to obtain product one. Product one is ball-milled and passed through a 1.18 mm sieve to obtain product two. 0 parts activator, 3 parts cement, 8 parts slag, 39 parts gravel, 11 parts water, and 50 parts of product two are mixed to obtain product three. Product three is placed into a 10cm*10cm*10cm cylindrical mold and then compacted by a press to a compaction degree of 95%. After standing for 24 hours, it is demolded using a demolding machine to obtain product four. After curing, product four is soaked in water for 24 hours on days 6, 27, and 89 and then tested accordingly.

[0035] Example 2: A method for preparing a phosphogypsum-based inorganic binder stabilized material, comprising 0.4 parts calcium oxide, 11 parts water, and 99.6 parts phosphogypsum, which are mixed to modify the phosphogypsum. After the gypsum modification pretreatment, the mixture is allowed to stand at room temperature for 24 hours and then dried in an oven at 80°C for 24 hours to obtain product one. Product one is ball-milled and passed through a 1.18 mm sieve to obtain product two. 0.11 parts sodium hydroxide activator, 3 parts cement, 8 parts slag, 39 parts gravel, 11 parts water, and 50 parts of product two are mixed to obtain product three. Product three is placed into a 10cm*10cm*10cm cylindrical mold and then compacted by a press to a compaction degree of 95%. After standing for 24 hours, it is demolded using a demolding machine to obtain product four. After curing, product four is soaked in water for 24 hours on days 6, 27, and 89 and then tested accordingly.

[0036] Example 3: A method for preparing a phosphogypsum-based inorganic binder stabilized material, comprising 0.4 parts calcium oxide, 11 parts water, and 99.6 parts phosphogypsum, which are mixed to modify the phosphogypsum. After the gypsum modification pretreatment, the mixture is allowed to stand at room temperature for 24 hours and then dried in an oven at 80°C for 24 hours to obtain product one. Product one is ball-milled and passed through a 1.18 mm sieve to obtain product two. 0.22 parts sodium hydroxide activator, 3 parts cement, 8 parts slag, 39 parts gravel, 11 parts water, and 50 parts of product two are mixed to obtain product three. Product three is placed into a 10cm*10cm*10cm cylindrical mold and then compacted by a press to a compaction degree of 95%. After standing for 24 hours, it is demolded using a demolding machine to obtain product four. After curing, product four is soaked in water for 24 hours on days 6, 27, and 89 and then tested accordingly.

[0037] Example 4: A method for preparing a phosphogypsum-based inorganic binder stabilized material, comprising 0.4 parts calcium oxide, 11 parts water, and 99.6 parts phosphogypsum, which are mixed to modify the phosphogypsum. After the gypsum modification pretreatment, the mixture is allowed to stand at room temperature for 24 hours and then dried in an oven at 80°C for 24 hours to obtain product one. Product one is ball-milled and passed through a 1.18 mm sieve to obtain product two. 0.33 parts sodium hydroxide activator, 3 parts cement, 8 parts slag, 39 parts gravel, 11 parts water, and 50 parts of product two are mixed to obtain product three. Product three is placed into a 10cm*10cm*10cm cylindrical mold and then compacted by a press to a compaction degree of 95%. After standing for 24 hours, it is demolded using a demolding machine to obtain product four. After curing, product four is soaked in water for 24 hours on days 6, 27, and 89 and then tested accordingly.

[0038] Example 5: A method for preparing a phosphogypsum-based inorganic binder stabilized material, comprising 0.4 parts calcium oxide, 11 parts water, and 99.6 parts phosphogypsum, which are mixed to modify the phosphogypsum. After the gypsum modification pretreatment, the mixture is allowed to stand at room temperature for 24 hours and then dried in an oven at 80°C for 24 hours to obtain product one. Product one is ball-milled and passed through a 1.18 mm sieve to obtain product two. 0.44 parts sodium hydroxide activator, 3 parts cement, 8 parts slag, 39 parts gravel, 11 parts water, and 50 parts of product two are mixed to obtain product three. Product three is placed into a 10cm*10cm*10cm cylindrical mold and then compacted by a press to a compaction degree of 95%. After standing for 24 hours, it is demolded using a demolding machine to obtain product four. After curing, product four is soaked in water for 24 hours on days 6, 27, and 89 and then tested accordingly.

[0039] Example 6: A method for preparing a phosphogypsum-based inorganic binder stabilized material, comprising 0.4 parts calcium oxide, 11 parts water, and 99.6 parts phosphogypsum, which are mixed to modify the phosphogypsum. After the gypsum modification pretreatment, the mixture is allowed to stand at room temperature for 24 hours and then dried in an oven at 80°C for 24 hours to obtain product one. Product one is ball-milled and passed through a 1.18 mm sieve to obtain product two. 0.11 parts calcium chloride activator, 3 parts cement, 8 parts slag, 39 parts gravel, 11 parts water, and 50 parts of product two are mixed to obtain product three. Product three is placed into a 10cm*10cm*10cm cylindrical mold and then compacted by a press to a compaction degree of 95%. After standing for 24 hours, it is demolded using a demolding machine to obtain product four. After curing, product four is soaked in water for 24 hours on days 6, 27, and 89 and then tested accordingly.

[0040] Example 7: A method for preparing a phosphogypsum-based inorganic binder stabilized material, comprising 0.4 parts calcium oxide, 11 parts water, and 99.6 parts phosphogypsum, which are mixed to modify the phosphogypsum. After the gypsum modification pretreatment, the mixture is allowed to stand at room temperature for 24 hours and then dried in an oven at 80°C for 24 hours to obtain product one. Product one is ball-milled and passed through a 1.18 mm sieve to obtain product two. 0.22 parts calcium chloride activator, 3 parts cement, 8 parts slag, 39 parts gravel, 11 parts water, and 50 parts of product two are mixed to obtain product three. Product three is placed into a 10cm*10cm*10cm cylindrical mold and then compacted by a press to a compaction degree of 95%. After standing for 24 hours, it is demolded using a demolding machine to obtain product four. After curing, product four is soaked in water for 24 hours on days 6, 27, and 89 and then tested accordingly.

[0041] Example 8: A method for preparing a phosphogypsum-based inorganic binder stabilized material, comprising 0.4 parts calcium oxide, 11 parts water, and 99.6 parts phosphogypsum, which are mixed to modify the phosphogypsum. After the gypsum modification pretreatment, the mixture is allowed to stand at room temperature for 24 hours and then dried in an oven at 80°C for 24 hours to obtain product one. Product one is ball-milled and passed through a 1.18 mm sieve to obtain product two. 0.33 parts calcium chloride activator, 3 parts cement, 8 parts slag, 39 parts gravel, 11 parts water, and 50 parts of product two are mixed to obtain product three. Product three is placed into a 10cm*10cm*10cm cylindrical mold and then compacted by a press to a compaction degree of 95%. After standing for 24 hours, it is demolded using a demolding machine to obtain product four. After curing, product four is soaked in water for 24 hours on the 6th, 27th, and 89th days and then tested accordingly.

[0042] Example 9: A method for preparing a phosphogypsum-based inorganic binder stabilized material, comprising 0.4 parts calcium oxide, 11 parts water, and 99.6 parts phosphogypsum, which are mixed to modify the phosphogypsum. After the gypsum modification pretreatment, the mixture is allowed to stand at room temperature for 24 hours and then dried in an oven at 80°C for 24 hours to obtain product one. Product one is ball-milled and passed through a 1.18 mm sieve to obtain product two. 0.44 parts calcium chloride activator, 3 parts cement, 8 parts slag, 39 parts gravel, 11 parts water, and 50 parts of product two are mixed to obtain product three. Product three is placed into a 10cm*10cm*10cm cylindrical mold and then compacted by a press to a compaction degree of 95%. After standing for 24 hours, it is demolded using a demolding machine to obtain product four. After curing, product four is soaked in water for 24 hours on days 6, 27, and 89 and then tested accordingly.

[0043] Example 10: A method for preparing a phosphogypsum-based inorganic binder stabilized material, comprising 0.4 parts calcium oxide, 11 parts water, and 99.6 parts phosphogypsum, which are mixed to modify the phosphogypsum. After the gypsum modification pretreatment, the mixture is allowed to stand at room temperature for 24 hours and then dried in an oven at 80°C for 24 hours to obtain product one. Product one is ball-milled and passed through a 1.18 mm sieve to obtain product two. 0.11 parts sodium carbonate activator, 3 parts cement, 8 parts slag, 39 parts gravel, 11 parts water, and 50 parts of product two are mixed to obtain product three. Product three is placed into a 10cm*10cm*10cm cylindrical mold and then compacted by a press to a compaction degree of 95%. After standing for 24 hours, it is demolded using a demolding machine to obtain product four. After curing, product four is soaked in water for 24 hours on days 6, 27, and 89 and then tested accordingly.

[0044] Example 11: A method for preparing a phosphogypsum-based inorganic binder stabilized material, comprising 0.4 parts calcium oxide, 11 parts water, and 99.6 parts phosphogypsum, which are mixed to modify the phosphogypsum. After the gypsum modification pretreatment, the mixture is allowed to stand at room temperature for 24 hours and then dried in an oven at 80°C for 24 hours to obtain product one. Product one is ball-milled and passed through a 1.18 mm sieve to obtain product two. 0.22 parts sodium carbonate activator, 3 parts cement, 8 parts slag, 39 parts gravel, 11 parts water, and 50 parts of product two are mixed to obtain product three. Product three is placed into a 10cm*10cm*10cm cylindrical mold and then compacted by a press to a compaction degree of 95%. After standing for 24 hours, it is demolded using a demolding machine to obtain product four. After curing, product four is soaked in water for 24 hours on days 6, 27, and 89 and then tested accordingly.

[0045] Example 12: A method for preparing a phosphogypsum-based inorganic binder stabilized material, comprising 0.4 parts calcium oxide, 11 parts water, and 99.6 parts phosphogypsum, which are mixed to modify the phosphogypsum. After the gypsum modification pretreatment, the mixture is allowed to stand at room temperature for 24 hours and then dried in an oven at 80°C for 24 hours to obtain product one. Product one is ball-milled and passed through a 1.18 mm sieve to obtain product two. 0.33 parts sodium carbonate activator, 3 parts cement, 8 parts slag, 39 parts gravel, 11 parts water, and 50 parts of product two are mixed to obtain product three. Product three is placed into a 10cm*10cm*10cm cylindrical mold and then compacted by a press to a compaction degree of 95%. After standing for 24 hours, it is demolded using a demolding machine to obtain product four. After curing, product four is soaked in water for 24 hours on days 6, 27, and 89 and then tested accordingly.

[0046] Example 13: A method for preparing a phosphogypsum-based inorganic binder stabilized material, comprising 0.4 parts calcium oxide, 11 parts water, and 99.6 parts phosphogypsum, which are mixed to modify the phosphogypsum. After the gypsum modification pretreatment, the mixture is allowed to stand at room temperature for 24 hours and then dried in an oven at 80°C for 24 hours to obtain product one. Product one is ball-milled and passed through a 1.18 mm sieve to obtain product two. 0.44 parts sodium carbonate activator, 3 parts cement, 8 parts slag, 39 parts gravel, 11 parts water, and 50 parts of product two are mixed to obtain product three. Product three is placed into a 10cm*10cm*10cm cylindrical mold and then compacted by a press to a compaction degree of 95%. After standing for 24 hours, it is demolded using a demolding machine to obtain product four. After curing, product four is soaked in water for 24 hours on days 6, 27, and 89 and then tested accordingly.

[0047] Experimental test:

[0048] Reference Figure 5The changes in unconfined compressive strength of phosphogypsum-based specimens at 7, 28, 90, and 180 days after the addition of different activators were investigated. As shown in the figure, the unconfined compressive strength of the phosphogypsum-based specimens significantly increased with the addition of activators. The best effect was observed at 7 days with a CaCl2 content of 0.22%, increasing the strength by 280.0%; at 28 days with a Na2CO3 content of 0.33%, the best effect was observed, increasing the strength by 137.8%; and at 90 and 180 days, the best effect was still observed with a CaCl2 content of 0.22%, increasing the strength by 82.9% and 79.5%, respectively. However, as the content of different activators increased to a certain extent, the strength of the specimens began to decrease. Further increases in the activator content eventually led to specimens with excessive activator having strengths almost the same as the baseline group. This trend indicates that, with proper use of activators, the strength of phosphogypsum-based specimens can be improved, meeting the requirements for Class II and above highways. However, excessive use is not advisable, especially when the activator content is low, as this can both increase the strength of the phosphogypsum-based specimens and save costs. With increasing curing time, the strength of specimens added after 180 days with NaOH, CaCl2, and Na2CO3 increased by 0.80%, 1.64%, and 0.11% respectively compared to 90 days. This shows that the increase in specimen strength over a long period is not significant. Therefore, a comprehensive comparison indicates that CaCl2 has the best effect on the strength of phosphogypsum-based specimens.

[0049] according to Figure 5 The trend of the curve was analyzed. Without the addition of an activator, phosphogypsum, which lacks cementing properties, filled the specimens as aggregate. After adding water, the substances in the specimens underwent a hydration reaction, generating a large amount of CSH gel and Ca(OH)2, initially providing strength. Secondly, the large amount of active SiO2 and Al2O3 in fly ash interacts with the Ca(OH)2 produced by cement hydration, generating hydrated calcium silicate and hydrated calcium aluminate. Calcium silicate hydrate can transform into a gel, while hydrated calcium aluminate continues to react with other substances to form ettringite, thus increasing strength. With the addition of an activator, the active substances in fly ash can be significantly activated, promoting chemical reactions, producing adhesion, and increasing strength. However, with the increase of the activator content, excessive ettringite is generated in the specimens and crystallizes in the pores, leading to an increase in pore volume and a decrease in strength. However, the addition of NaOH consistently showed a decreasing trend. Therefore, to ensure the optimal NaOH content, several additional sets of experiments were conducted, and the unconfined compressive strength was measured as follows: Figure 6 As shown, the optimal NaOH content is 0.066%.

[0050] Reference Figure 7As shown, the experimental results of the optimal NaOH content show that the optimal NaOH content for splitting strength is consistent with the optimal NaOH content for unconfined compressive strength. Furthermore, based on... Figure 6 It can be seen that with the increase of activator content, the increase in splitting strength in the later stage is significantly limited, and the change is relatively slow with age, tending to a stable state. Analysis of the results suggests that this is mainly due to the large amount of phosphogypsum and the low proportion of cementitious materials. Less phosphogypsum is needed to participate in the chemical reaction to form ettringite, but a larger proportion of phosphogypsum acts as aggregate to fill the pores of the inorganic binder, resulting in a weakened overall bonding effect of the inorganic binder and thus a significant difference in splitting strength.

[0051] Reference Figure 8 Several optimal groups of phosphogypsum-based specimens with different activators were selected for wet-dry cycle tests to investigate the mass loss rate of the specimens under different activators under wet-dry cycle conditions. As shown in the figure, the mass loss rate of the phosphogypsum-based specimens with different activators continuously increases with the increase of the number of wet-dry cycles, showing an increasing trend, reaching a maximum of nearly 5%. According to the standard test method for wet-dry compacted soil-cement mixtures, for granular mixtures, a weight loss of less than 14% indicates that the material has resistance to wet / dry effects. Therefore, NaOH, CaCl2, and Na2CO3, these three activators, exhibit resistance to wet / dry effects when added to phosphogypsum-based specimens. (Refer to...) Figure 9 After 6 and 12 wet-dry cycles, the compressive strength of the activator-phosphogypsum-based specimens changed little, as shown in the figure. This indicates that the specimens have a strong ability to resist damage caused by changes in external moisture and have a better ability to adapt to the external environment compared with traditional materials.

[0052] Reference Figure 10 Phosphogypsum was pretreated using a quicklime neutralization method. Considering the small amount of quicklime added, some impurities may still remain in the pretreated phosphogypsum. Therefore, the content of some trace elements was tested to characterize its environmental impact. The content of phosphorus (F) did not change significantly with curing conditions, but the content of chlorine (Cl) was higher due to the addition of CaCl2. (Refer to...) Figure 11 After a period of time, some of the unneutralized phosphorus will dissolve from the sample into the water. However, once it reaches a certain level, it will reach equilibrium and the content will not increase further. Moreover, the phosphorus content is extremely low, below the national standard. Therefore, it can be concluded that the material has minimal environmental impact during use and will not pose a significant problem under the washout of rainwater, thus meeting safety standards.

[0053] Reference Figure 12The images show SEM images of inorganic binder stabilized material specimens for road base courses with different activators. The images reveal CSH gel and ettringite crystals attached to the gel, as well as some hexagonal plate-shaped Ca(OH)₂ crystals. The images also show that the internal structure of the material generated in the specimen with the added activator is relatively denser than that in the specimen without the added activator. As the reaction proceeds, the generated material fills the internal pores of the specimen and encapsulates the surrounding material, preventing the reaction from continuing and resulting in insufficient strength enhancement in the later stages. This also demonstrates that at certain activator concentrations, excessive reaction-generated material within the specimen leads to structural damage and reduced strength.

[0054] The experimental data above shows that the inorganic binder stabilizing material for the road base layer in this technical solution uses phosphogypsum and gravel as the stabilized materials, and cement and fly ash as the binders. The stabilized materials account for about 90% of the total stabilizing material. Among them, fly ash has low activity, and its cementing effect is much weaker than that of cement. There is very little direct chemical reaction between phosphogypsum and fly ash, and cement remains the main material that dominates the curing of phosphogypsum in the entire system. Without the addition of an activator, the chemical reaction between cement and fly ash forms the early strength basis of the material system. Mechanical compaction makes the mixture more compact and increases the contact area between water and the binder, accelerating binder hydration. The abundant active SiO2 and Al2O3 components in fly ash interact with Ca(OH)2 produced during cement hydration, forming hydrated calcium silicate and hydrated calcium aluminate. Calcium silicate can transform into a gel, while hydrated calcium aluminate can continue to react with phosphogypsum slurry to form ettringite. However, the cement-to-fly ash ratio is relatively low, resulting in insufficient alkaline environment for hydration and a slow hydration process. Therefore, the addition of an activator provides a sufficiently strong alkaline environment to activate the cement and fly ash, promoting their hydration and producing a large amount of hydrated calcium aluminate. Subsequently, phosphogypsum reacts with this hydrate to form ettringite crystals, significantly enhancing the strength of the material system. However, when a large amount of activator is used, as some of the water in the material system slowly evaporates, the alkaline substances dissolved in the water are carried to the surface of the material and gradually deposit into a layer of white substance, which damages the material properties and leads to a decrease in strength. Figure 13 As shown.

[0055] The effects of different activators on the inorganic binder system of phosphogypsum-based pavement base layers differ as follows: 1. NaOH and phosphogypsum react to form calcium hydroxide gel, which binds the solid particles of phosphogypsum, thereby increasing the strength of the specimen. 2. Calcium carbonate and sodium sulfate crystals formed by Na2CO3 and phosphogypsum cover the surface of the solid particles of phosphogypsum and simultaneously coagulate with the formed silica gel, thus increasing the strength of the specimen. However, excessive addition of NaOH and Na2CO3 leads to an excessively high alkaline environment inside the specimen, exceeding the alkaline environment required by ettringite, causing the ettringite to be destroyed and the strength to decrease. 3. CaCl2 has the best strength-enhancing effect on inorganic binders. The reason for this may be that CaCl2 not only activates the active substances in fly ash but also provides a good alkaline environment for ettringite. When a large amount of ettringite forms and encapsulates the phosphogypsum, preventing the reaction from proceeding, CaCl2 provides the necessary alkaline environment for the reaction. 2+ This allows the reaction to continue, thus increasing its strength. However, the reason why excessive CaCl2 provides a decrease in strength is not only because the excessive CaCl2 content leads to an excessively alkaline environment, exceeding the alkalinity required by ettringite and causing its destruction and reduced strength; but also because CaCl2 provides a large amount of Ca... 2+ This results in excessive formation of ettringite, which damages the internal structure of the specimen and leads to a decrease in strength.

[0056] In summary, this technical solution uses phosphogypsum as the main raw material, along with cement, fly ash, and gravel, as raw materials. After adding an activator, an inorganic binder stabilized material for road base courses is prepared. With the addition of the activator, the performance of the phosphogypsum-based road base inorganic binder stabilized material specimens initially increases and then gradually decreases. CaCl2 has the best strength-enhancing effect on the inorganic binder, with an optimal content of 0.22%; followed by NaOH, with an optimal dosage of 0.11%; and then Na2CO3, with an optimal dosage of 0.33%. Their 7-day compressive strength increased by 280.0%, 276.2%, and 161.3% respectively compared to the blank control group, all meeting the requirements for use on Class II and above highways.

[0057] Simultaneously, phosphogypsum reacts with the cementing material to form ettringite crystals. These crystals interlock to form a dense network structure, creating a framework that gives the material strength. Excess phosphogypsum acts as aggregate, filling the internal pores of the material. Eettringite crystals have high strength and are insoluble in water; therefore, the ettringite framework effectively encapsulates unreacted phosphogypsum, reducing the leaching of harmful substances. Furthermore, because the formation of ettringite is a slow process, requiring a considerable amount of time, the early strength is not very high. An activator is needed to initiate the chemical reaction; therefore, the addition of an activator significantly improves the material's strength.

[0058] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.

Claims

1. A method for preparing a phosphogypsum-based inorganic binder stabilized material, characterized in that: Includes the following steps: S1: Pretreatment of phosphogypsum: Phosphogypsum was modified and pretreated with calcium oxide and then dried to obtain product one; S2: Ball milling and sieving: Product 1 is ball-milled and then sieved to obtain Product 2; S3: Preparation of phosphogypsum-based inorganic binder: The raw materials, product two and activator are mixed to obtain product three. The activator is one of NaOH, CaCl2 and Na2CO3. After product three is placed in a mold and compacted, it is demolded to obtain product four. S4: Curing of phosphogypsum-based inorganic binder stabilized material: After curing the product, corresponding tests were conducted after soaking in water for 24 hours on days 6, 27, and 89.

2. The method for preparing a phosphogypsum-based inorganic binder stabilized material according to claim 1, characterized in that: In S1, the phosphogypsum has a water content of 12.9% and a pH of 2.

75. The phosphogypsum crystals mainly exhibit regular flaky or prismatic crystals with a particle size distribution between 5 and 100 μm and an average particle size of 45 to 75 μm.

3. The method for preparing a phosphogypsum-based inorganic binder stabilized material according to claim 1, characterized in that: In S1, 0.4 parts of calcium oxide and 11 parts of water are mixed to modify 99.6 parts of phosphogypsum. After the gypsum modification pretreatment, it is allowed to stand at room temperature for 24 hours and then dried in an oven at 80°C for 24 hours.

4. The method for preparing a phosphogypsum-based inorganic binder stabilized material according to claim 1, characterized in that: In step S2, product one is ball-milled using a ball mill and passed through a 1.18mm sieve.

5. The method for preparing a phosphogypsum-based inorganic binder stabilized material according to claim 1, characterized in that: In S3, the raw materials include 3 parts cement, 8 parts slag, 39 parts gravel, and 11 parts water. In S3, the product is 50 parts and the activator is 0-1 parts.

6. The method for preparing a phosphogypsum-based inorganic binder stabilized material according to claim 5, characterized in that: The slag is selected from a concrete mixing plant and is a white powder; the gravel is black gravel aggregate purchased from the market; and the cement is a common hydraulic cementitious material, specifically P·O42.5 silicate cement.

7. The method for preparing a phosphogypsum-based inorganic binder stabilized material according to claim 5, characterized in that: The activator is preferably one of 0.11 parts, 0.22 parts, 0.33 parts, or 0.44 parts; sodium hydroxide, AR analytical grade, 96%, white crystalline powder; calcium chloride, AR analytical grade, 96%, white powder; sodium carbonate, inorganic compound, AR analytical grade, ≥99.5%, white odorless powder or granules at room temperature.

8. The method for preparing a phosphogypsum-based inorganic binder stabilized material according to claim 1, characterized in that: In step S3, product three is placed into a cylindrical mold of 10cm*10cm*10cm, then compacted by a press to a compaction degree of 95%, left to stand for 24 hours, and then demolded by a demolding machine to obtain product four.

9. The method for preparing a phosphogypsum-based inorganic binder stabilized material according to claim 1, characterized in that: In step S4, after the product has been cured for four days, it is soaked in water for 24 hours on days 6, 27, and 89. The test block is then taken out and placed in water for immersion, with the water level 2 cm above the surface of the test block. After soaking for one day, the test block is taken out, the surface moisture is wiped dry with a cloth, and then placed on a press for compressive strength testing.

10. The method for preparing a phosphogypsum-based inorganic binder stabilized material according to claim 1, characterized in that: The tests for the phosphogypsum-based inorganic binder stabilized material include unconfined compressive strength test, splitting tensile strength test, and wet-dry cycle test.